Web-Based Priority Program Recommendation Using Collaborative Filtering: Rekomendasi Program Prioritas Berbasis Web Menggunakan Collaborative Filtering - Pesik, Luisa Maria; Tinambunan, Medi Hermanto; Santa, Kristofel (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Recess activities of regional legislative members function as a formal mechanism for collecting diverse public aspirations related to regional development programs. Specific Background: In Minahasa Regency, the determination of priority programs derived from recess activities has traditionally relied on manual procedures that are prone to subjectivity and inconsistency. Knowledge Gap: Despite extensive studies on collaborative filtering in various domains, its application for managing and prioritizing legislative recess programs within local government contexts remains limited. Aims: This study aims to design and implement a web-based priority program recommendation system for DPRD recess activities using an Item-Based Collaborative Filtering algorithm. Results: The system was developed using the Waterfall method and implemented with PHP and MySQL, incorporating modules for aspiration management, rating, authentication, and recommendation generation. Black box testing across core functionalities confirmed that the system operated according to specifications and supported structured priority ranking of programs. Novelty: The research introduces the application of Item-Based Collaborative Filtering to DPRD recess aspiration management, replacing a previously manual and subjective process. Implications: The proposed system provides a structured, transparent, and data-driven approach to supporting legislative decision-making in prioritizing public programs at the regional level. Highlights• The developed system organizes recess aspirations into measurable program priorities• Item-based recommendation logic supports consistent ranking of proposed programs• Web-based architecture enables structured management of legislative aspiration data KeywordsCollaborative Filtering; Recommendation System; DPRD Recess; Priority Program; Web-Based Application